2019
DOI: 10.1016/j.jalz.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Emerging cerebrospinal fluid biomarkers in autosomal dominant Alzheimer's disease

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Potential Conflicts of Interest S.E.S. has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 54 publications
9
98
1
Order By: Relevance
“…The MC for which levels of YKL-40 were available had an average of 12 years left to the expected onset of first clinical symptoms, while the MC subgroup, having enough sample volume to analyze neurogranin as well, had an average of 10 years left to expected symptom onset. Regarding CSF YKL-40, these results are not in concordance with the results of a large study on CSF biomarkers in the Dominantly Inherited Alzheimer Network (DIAN), which showed an increase in CSF YKL-40 in FAD mutation carriers 15-19 years before the expected onset of clinical symptoms [60]. No presymptomatic change in CSF neurogranin was observed in the DIAN study, which is in agreement with the result obtained in the current study.…”
Section: Discussioncontrasting
confidence: 55%
“…The MC for which levels of YKL-40 were available had an average of 12 years left to the expected onset of first clinical symptoms, while the MC subgroup, having enough sample volume to analyze neurogranin as well, had an average of 10 years left to expected symptom onset. Regarding CSF YKL-40, these results are not in concordance with the results of a large study on CSF biomarkers in the Dominantly Inherited Alzheimer Network (DIAN), which showed an increase in CSF YKL-40 in FAD mutation carriers 15-19 years before the expected onset of clinical symptoms [60]. No presymptomatic change in CSF neurogranin was observed in the DIAN study, which is in agreement with the result obtained in the current study.…”
Section: Discussioncontrasting
confidence: 55%
“…6 of 13 EMBO Molecular Medicine 11: e11170 | 2019 ª 2019 The Authors earlier change in Ab42 is not supported by a recent study on autosomal dominant AD (Schindler et al, 2019). The Ab40 finding should also be interpreted cautiously since this initial decline was driven by few individuals and the Ab40 model was barely significant for CSF (P = 0.02; Appendix Fig S1) and was not significant for plasma (P = 0.37; Appendix Fig S2).…”
Section: Discussionmentioning
confidence: 82%
“…increased NFL: most strongly associated with the dementia stage of AD ▪ These are complementary to each other in AD clinical staging CSF neurogranin, NFL 94 ▪ NFL: highest accuracy in prediction of MCI conversion to AD compared to neurogranin, Aβ 42 , pTau 181 , and tTau levels, on >1 yr FU CSF neurogranin, SNAP-25, VILIP-1, YKL-40 9,98 ▪ commonly cooccur with AD 7 , considering both diseasespecific and more general biomarkers of pathology may increase the likelihood of realizing efficient diseasemodifying therapeutics. This approach could lead to more efficient treatment regimens and allow monitoring of the response to treatment on an individual patient basis, which is important given the diversity of AD pathology.…”
Section: Perspective On the Utility Of New Biomarkersmentioning
confidence: 96%